2016
DOI: 10.1111/fcp.12220
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus sabdariffa increases hydroxocobalamin oral bioavailability and clinical efficacy in vitamin B12 deficiency with neurological symptoms

Abstract: The aim of the study was to evaluate the bioavailability and clinical benefits of oral new formulation (HB ) of hydroxocobalamin (Hdrx) with Hibiscus sabdariffa (HS). First, in an observational study, a cohort of 30 vitamin B -deficient patients (vit B < 200 pg/mL) with neurological symptoms received oral fixed dose of Hdrx containing 15 mg Hdrx daily for 10 days followed by 15 mg monthly. Clinical benefits were evaluated on haematological and biochemical parameters, and neurological improvement at days 10 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Pathophysiological occurrences arising from intracellular homocysteine molecules are one of the factors that can cause NAFLD [ 20 ]. Increased homocysteine can be caused by a vitamin B12 deficiency; vitamin B12 acts as an enzyme cofactor for methionine synthase [ 21 ]. Increased plasma homocysteine levels cause oxidative stress, a lack of methyl donors, misfolded proteins and hepatic reticulum stress [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiological occurrences arising from intracellular homocysteine molecules are one of the factors that can cause NAFLD [ 20 ]. Increased homocysteine can be caused by a vitamin B12 deficiency; vitamin B12 acts as an enzyme cofactor for methionine synthase [ 21 ]. Increased plasma homocysteine levels cause oxidative stress, a lack of methyl donors, misfolded proteins and hepatic reticulum stress [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two case reports hinted at the possibility of benefit from interaction, one interaction checker reported two interactions as beneficial (albeit in opposition to case report findings), and two clinical studies reported benefit from interaction. Perhaps the ability of botanical constituents to decrease pharmaceutical drug clearance could be harnessed to reduce drug costs through reduction in dose requirements, lower the burden of drug excretion into the water supply, or enhance bioavailability of nutrients [ 53 , 54 ]. Further exploration could conceivably improve patient quality of life through reduction in side effects [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jejunum samples were excised, rinsed in isotonic Ringer's solution, and cut flat open through the mesenteric axis. The jejunum slices were then mounted in Ussing chambers in line with established procedure [9,10].…”
Section: Animalsmentioning
confidence: 99%